Resonance-based approach for section flexural rigidity identification of simply supported beams. (1st June 2021) - Pan, Danguang; Feng, Zhiyao; Lu, Pan; Zheng, Zijian; Zhao, Bincheng
Highlights: A resonance-based approach is proposed to evaluate section flexural stiffness. The method is suitable for arbitrary non-uniform beams. Equivalent load–deflection response can be achieved with a small fraction of the static load for the proposed method. Tests on a cracked concrete beam and a non-uniform steel beam are completed to verify the validity. Abstract: Deteriorated sections decide the bearing capacity of beams. Because reinforced concrete beams are nonhomogeneous materials and often have variable sections along the beam, it is a challenge to precisely measure flexural rigidity of damage or repaired sections. This paper proposes a resonance-based non-destructive approach to identify section flexural rigidity for non-uniform simply supported beams. In the method, the resonant force is applied to the beam at the mid-span to measure the accelerations of evenly spaced segments and the strains of sections. The amplitude of the mid-span displacement is limited to approximately 1/10 4 of the span to avoid new damage. The proposed method can transform the calculation of dynamic bending moment and curvature into an equivalent static calculation to formulate a straightforward algorithm and easy-to-use equation on section flexural rigidity. It is applicable to non-uniform simply supported beams with arbitrary stiffness distribution. Theoretical and test results of a reinforced concrete and a non-uniform steel beam show that the identified section flexural rigidity would converge the exact result with the increased numbers of evenly spaced segments, and no less than five evenly spaced segments are sufficient in engineering applications.